Enterocolic lymphocytic phlebitis as a newly recognized manifestation of IgG4-related disease - Laco, Jan; Örhalmi, Július; Bártová, Jolana; Zimandlová, Dana (International journal of surgical pathology, 2015)
Herein we present a case of a 65-year-old woman with enterocolic lymphocytic phlebitis (ELP) who presented with anemic syndrome and in whom severe stenosis of the right flexure of large bowel was detected. The microscopic examination revealed fibrosis of the submucosa and lymphoplasmacytic phlebitis of small veins and venules, whereas arteries were spared. There were 110 IgG4-positive and 160 IgG-positive plasma cells in 1 high-power field, respectively, with corresponding IgG4/IgG ratio of 0.69. The IgG4 serum level was 2.42 g/L. According to the currently proposed criteria, this ELP case is the first that may be diagnosed as definite IgG4-related disease (IgG4-RD). Although based on the sole case description, taken together with a recent review and a case report, we presume that a subset of ELPs is a manifestation of IgG4-RD.
Keywords: nemoci imunitního systému; Enterocolitis; Aged; Female; Immune System Diseases; flebitida; enterocolic lymphocytic phlebitis; IgG4; Humans; ženské pohlaví; IgG4-related disease; senioři; lidé; Immunoglobulin G; Phlebitis; bowel; imunoglobulin G; enterokolitida